Analisis Pelaksanaan Penanganan Tindak Pidana Korupsi Bantuan Langsung Tunai Dana Desa Pada Masa Pandemi Corona Virus Desease di Kabupaten Musi Rawas - Syuroh, Mat; Mardianto, Mardianto; Marliansyah, Marliansyah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
The purpose of this study was to analyze the Implementation of the Handling of Corruption Crimes Direct Cash Assistance of Village Funds During the Corona Virus Disease Pandemic in Musi Rawas Regency. This study uses a qualitative descriptive analysis technique. Based on the results of research and discussion in the previous chapter, the following conclusions can be drawn: (1). The plan consists of the dimensions of the target to be achieved, namely the prevention of criminal acts of corruption in direct cash assistance from village funds carried out by elements of the village apparatus, then the dimensions of the regulations used in this activity, namely Law Number 31 of 1999 in conjunction with Law No. Number 20 of 2001 concerning Eradication of criminal acts of corruption. (2). For the organizing dimension, the indicators for implementing human resources are 8 people, the organizational structure decided by the Head of the Resort Police regarding the organizational structure of the Mura Police Criminal Investigation Unit, the division of labor in accordance with the main tasks, and the positions held by each existing personnel. (3) The dimensions of implementation for the process and mechanism for handling corruption in direct cash assistance from village funds during the corona virus disease pandemic in Musi Rawas Regency follow established procedures and procedures, namely in accordance with applicable laws and regulations. (4). The supervisory dimension for the supervisory stage is the existence of external supervision and internal supervision in the Implementation of Handling Corruption Crimes Direct Village Fund Cash Assistance During the Corona Virus Disease Pandemic in Musi Rawas Regency.